The Florida Agricultural Handbook of Solid and Hazardous Waste Regulation: Introduction - Michael T. Olexa; Damian C. Adams; Kathleen Maurer (EDIS)
Circular 1139 helps Floridians recognize which agricultural and household activities may involve solid and hazardous wastes. It also provides an introduction to the agencies and statutes that govern solid and hazardous waste disposal.